Spatiotemporal Analysis of B Cell- and Antibody Secreting Cell-Subsets in Human Melanoma Reveals Metastasis-, Tumor Stage-, and Age-Associated Dynamics - Chen, Minyi; Werner, Franziska; Wagner, Christine; Simon, Martin; Richtig, Erika; Mertz, Kirsten D.; Griss, Johannes; Wagner, Stephan N. (Frontiers in Cell and Developmental Biology, 2021)
Background: The role of tumor-associated B cells in human cancer is only starting to emerge. B cells typically undergo a series of developmental changes in phenotype and function, however, data on the composition of the B cell population in human melanoma are largely absent including changes during tumor progression and their potential clinical significance. Methods: In this study, we compared the number and distribution of six major B cell and antibody secreting cell subpopulations outside tertiary lymphoid structures in whole tumor sections of 154 human cutaneous melanoma samples (53 primary tumors without subsequent metastasis, 44 primary tumors with metastasis, 57 metastatic samples) obtained by seven color multiplex immunohistochemistry and automated tissue imaging and analysis. Results: In primary melanomas, we observed the highest numbers for plasmablast-like, memory-like, and activated B cell subtypes. These cells showed a patchy, predominant paratumoral distribution at the invasive tumor-stroma margin. Plasma cell-like cells were hardly detected, germinal center- and transitional/regulatory-like B cells not at all. Of the major clinicopathological prognostic factors for primary melanomas, metastasis was associated with decreased memory-like B cell numbers and a higher age associated with higher plasmablast-like cell numbers. When we compared the composition of B cell subpopulations in primary melanomas and metastatic samples, we found a significantly higher proportion of plasma cell-like cells at distant metastatic sites and a higher proportion of memory-like B cells at locoregional than distant metastatic sites. Both cell types were detected mainly in the para- and intratunoral stroma. Conclusion: These data provide a first comprehensive and comparative spatiotemporal analysis of major B cell and antibody secreting cell subpopulations in human melanoma and describe metastasis-, tumor stage- and age-associated dynamics, an important premise for B cell-related biomarker and therapy studies.